BBC Radio Ulster’s Talkback Phone-in: Public Feedback in a Divided Public Space - Coleman, Stephen (Javnost-The Public, 1998)
This article is based upon extensive research of the BBC Radio Ulster daily phone-in programme, Talkback. The wider research is investigating the role of phone-in programmes as a contemporary public sphere for democratic debate. This article places the Talkback phone- ins within the specific context of a contested society within which two “publics” seek to assert their separate identities. The relationship between on-air public talk and official political talks is considered. The socio-political functions of phone-in talk are considered empirically (within the confines of limited space) and it is argued theoretically that talk on Talkback is addressed to one of three publics: ones own public; the divided public; and the imagined consensual public (which is addressed mainly by the BBC.)